A study of comparison between quality of life early closure of ileostomy and late closure of ileostomy - Neeraj Kumar Banoria; Pankaj Saunakiya; Muktesh Kumar Maurya (Asian Journal of Medical Sciences, 2023)
Background: In the developed countries, ileostomy is mainly constructed as a protective cover for distal colorectal or ileoanal pouch anastomosis, but in developing countries, it is still often made in emergency surgical settings where infective conditions such as enteric or tubercular perforations are common and patients present late in their course of illness which precludes primary closure. Aims and Objectives: The aim of the present study is to compare health-related quality of life at 3, 6, and 12 months comparing early versus late closure of a temporary ileostomy. Materials and Methods: The study was conducted on 50 patients, 25 patients undergoing for early stoma closure and 25 patients undergoing for late closure ileostomy each in Maharani Laxmi Bai Medical College, Jhansi, between January 2020 and June 2021. Results: The mean age of patient undergoing early closure is 36.16 and mean age of patient undergoing late closure is 40.36, out of which 80% were male patient and 20% patient were female. Using SF-36 questionnaire, out of 8 domains, quality of life of early closure of ileostomy is significantly better in respect of 3 domains and that is physical functioning – P=0.004. Mean±SD score for early stoma closure 80.6±22.495 for late closure 73.00±25.247. Social functioning P=0.05. Mean±SD score for early stoma closure, 74.00±4.243 late stoma closure 71.50 ±0.707. Role emotion P=0.04, Mean±SD score for early stoma closure 80.00±4.00 late closure 74.67±12.20. Conclusion: We concluded that quality of life in early closure of ileostomy is significantly better in respect of 3 domains (physical functioning, social functioning, and role emotion) out of 8 domains in SF-36 questionnaire than quality of life in late closure of ileostomy.